2021
DOI: 10.1016/j.cub.2021.04.072
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of hippocampal learning in human infants

Abstract: Highlights d Hippocampus supports statistical learning of temporal regularities in infancy d Changes in hippocampal activity emerge after only minutes of exposure d Localization of learning effects within hippocampal system similar to adults d Exploratory analyses suggest a selective role for medial prefrontal cortex

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 55 publications
6
49
0
Order By: Relevance
“…We found that the effect of predictability is reflected in every recorded region. This pattern of results provides evidence for a) the frontal lobe involvement in sequential learning and replicates and extends previous work with younger infants using EEG using a very similar paradigm (Basirat et al, 2014) and adds to broader evidence that the frontal lobe is involved in various types of learning in infancy including statistical learning (Ellis et al, 2021), audiovisual associative learning (Emberson et al, 2015;Kersey and Emberson, 2017;Kouider et al, 2015); b) provides from suggestive evidence that these learning based changes are not constrained to the frontal lobe but are also present in posterior perceptual cortices suggesting a role for the frontal lobe and feedback neural connections in these posterior changes; c) that the infant brain is highly plastic and readily shaped through experience with patterns and relatedly learning.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We found that the effect of predictability is reflected in every recorded region. This pattern of results provides evidence for a) the frontal lobe involvement in sequential learning and replicates and extends previous work with younger infants using EEG using a very similar paradigm (Basirat et al, 2014) and adds to broader evidence that the frontal lobe is involved in various types of learning in infancy including statistical learning (Ellis et al, 2021), audiovisual associative learning (Emberson et al, 2015;Kersey and Emberson, 2017;Kouider et al, 2015); b) provides from suggestive evidence that these learning based changes are not constrained to the frontal lobe but are also present in posterior perceptual cortices suggesting a role for the frontal lobe and feedback neural connections in these posterior changes; c) that the infant brain is highly plastic and readily shaped through experience with patterns and relatedly learning.…”
Section: Discussionsupporting
confidence: 85%
“…Humans are highly sensitive to statistical information and learn from statistical information incidentally starting early in infancy (need citations). While behavioral studies have made significant progress in understanding the computational mechanisms that underlie statistical learning (Siegelman et al, 2019;Thiessen, 2017), the underlying neural mechanisms that support statistical learning are not yet well understood (Schapiro et al, 2012;Turk-Browne et al, 2009) and there is even less known about the brain regions involved in statistical learning in infants (though see Ellis et al, 2021;Emberson et al, 2015;Kabdebon et al, 2015;Kersey and Emberson, 2017). Importantly, understanding the neural mechanisms supporting statistical learning in infancy will shed light on the mechanisms supporting development, and provide a foundation upon which we can investigate how these learning mechanisms change across conditions, stimuli and over development.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been suggested that there are two separate, specialized circuits for learning within the hippocampus (Schapiro et al, 2017) that support slower learning of general groups and rapid encoding of specific associations, respectively. While we would expect based on recent findings that the hippocampus would be engaged during statistical learning in infancy (Ellis et al, 2021), it may be through a restricted circuitry relative to adults. Namely, the intra-hippocampal pathways develop at different rates , indicating that perhaps only memory for general groups (via the monosynaptic pathway) would be available to infants (Gomez, 2016;Gómez & Edgin, 2016;Schapiro et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we used a visual statistical learning paradigm-shown to involve the hippocampus both among adults (Schapiro et al, 2012(Schapiro et al, , 2014(Schapiro et al, , 2016 and in development (Ellis et al, 2021;Finn et al, 2019;Schlichting et al, 2016)-to assess the formation of memory for both the specific associations and higher-order relationships embedded within the same experience. We presented participants with a continuous stream of simple shapes shown one at a time.…”
mentioning
confidence: 99%
“…Brain networks expand in cycles reminiscent of intellectual development . Bayesian rule extraction may start from as early as 3 months of age in anterior hippocampus, even before episodic memories are formed (Ellis et al, 2021), laying the ground for building blocks of LoT, when connections with the medial prefrontal cortex are established.…”
Section: Where Does Change In G Come From?mentioning
confidence: 99%